2020
DOI: 10.1186/s12889-020-09622-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of knowledge, skills and practices of insulin storage and injection handling techniques of diabetic patients in Ethiopian primary hospitals

Abstract: Background Insulin is an effective therapeutic agent in the management of diabetes, but also sensitive to the external environment. Consequently, diabetic patients’ adherence to insulin delivery recommendations is critical for better effectiveness. Patients’ lack of knowledge, skill and irrational practices towards appropriate insulin delivery techniques may end up in therapeutic failure and increase costs of therapy. The aim of this study was to evaluate patients’ knowledge, skills and practices of insulin st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
2
13
0
4
Order By: Relevance
“…In our study, pilgrims had just above average knowledge regarding insulin storage, and only 8.6% were deemed to have a good level of knowledge. These results are in line with numerous other studies reporting that diabetic patients lack appropriate knowledge and practice regarding insulin therapy, including storage, handling, and disposal of the medication and its associated consumables [ 25 – 27 ]. Using a similar cut of criteria for good knowledge as ours (knowledge score > 0.75), studies from India and Ethiopia reported that only 4% and 31.3% of participants, respectively, had good knowledge regarding insulin therapy [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, pilgrims had just above average knowledge regarding insulin storage, and only 8.6% were deemed to have a good level of knowledge. These results are in line with numerous other studies reporting that diabetic patients lack appropriate knowledge and practice regarding insulin therapy, including storage, handling, and disposal of the medication and its associated consumables [ 25 – 27 ]. Using a similar cut of criteria for good knowledge as ours (knowledge score > 0.75), studies from India and Ethiopia reported that only 4% and 31.3% of participants, respectively, had good knowledge regarding insulin therapy [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with numerous other studies reporting that diabetic patients lack appropriate knowledge and practice regarding insulin therapy, including storage, handling, and disposal of the medication and its associated consumables [ 25 – 27 ]. Using a similar cut of criteria for good knowledge as ours (knowledge score > 0.75), studies from India and Ethiopia reported that only 4% and 31.3% of participants, respectively, had good knowledge regarding insulin therapy [ 25 , 26 ]. Our results are concerning given that lack of insulin knowledge and inappropriate storage of the medication have been linked to poor glycemic control among diabetic patients [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Level of education, having an underlying health condition, and receiving health education on mediation storage were independently associated with good knowledge. Level of education is associated with better knowledge of medications, their handling and storage [23][24][25][26]. Being educated enables patients to understand and practice the written and oral guidelines and instructions of medication use, storage and handling better than those who are illiterate.…”
Section: Discussionmentioning
confidence: 99%
“…Only 28.2% of pilgrims accessed information on medication storage from the medication label in the current study. Studies have shown that not all medication users consult the medication label or the package insert for information [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In one study among Hajj pilgrims, only 54.2% reported that they do read the information on medications' labels before using them.…”
Section: Discussionmentioning
confidence: 99%